2019
DOI: 10.1186/s13046-019-1074-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 as a potential therapeutic target for aberrant NF-κB-driven distant metastasis of gastric cancer

Abstract: BackgroundDysregulated miR-7 and aberrant NF-κB activation were reported in various human cancers. However, the expression profile, clinical relevance and dysregulated mechanism of miR-7 and NF-κB RelA/p65 in human gastric cancers (GC) metastasis remain largely unknown. This study is to investigate the expression profile, clinical relevance and dysregulated mechanism of miR-7 and NF-κB RelA/p65 in GC and to explore the potential therapeutic effect of miR-7 to GC distant metastasis.MethodsTCGA STAD and NCBI GEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 32 publications
0
90
1
Order By: Relevance
“…Nuclear factor κB (NF‐κB) is a nuclear transcription factor which regulates expression of a large number of genes critical for the regulation of apoptosis, tumorigenesis, inflammation, and various autoimmune diseases . The NF‐κB signaling pathway is modulated by several miRNAs in certain types of cancers as previously reported . Thus, we examined whether the NF‐κB signaling pathway was regulated by miR‐148b in NSCLC.…”
Section: Introductionmentioning
confidence: 83%
“…Nuclear factor κB (NF‐κB) is a nuclear transcription factor which regulates expression of a large number of genes critical for the regulation of apoptosis, tumorigenesis, inflammation, and various autoimmune diseases . The NF‐κB signaling pathway is modulated by several miRNAs in certain types of cancers as previously reported . Thus, we examined whether the NF‐κB signaling pathway was regulated by miR‐148b in NSCLC.…”
Section: Introductionmentioning
confidence: 83%
“…To be noted, many studies indicate a tumor-suppressive role for miR-7, and its downregulation is correlated with poor prognosis in cancer patients [48][49][50]. Studies have confirmed that miR-7 can inhibit the growth of various types of cancer cells through a variety of key molecular pathways [51,52]. miR-7 also directly targets insulin-like growth factor 1 receptor (IGF1R) [53], FAK [54], and PAK1 [55], which can inhibit the proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of tumor cells.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…MiR-7, miR-9, and miR-508-3p act as tumor suppressors by inhibiting the NF-κB pathway [37,74,75]. Information regarding miR-216a is contradictory.…”
Section: Micrornas Associated With Gc Metastasis and Signaling Pathwamentioning
confidence: 99%
“…By inhibiting its target mTOR (PI3K/AKT/mTOR pathway), miR-7 induces apoptosis and suppresses tumor growth in in vivo experiments [36]. As a result of suppression of its target RELA, miR-7 inhibits the NF-κB signaling pathway and genes associated with metastasis: VNT, ICAM-1, VCAM-1, MMP-2, MMP-9, and VEGF [37].…”
Section: Introductionmentioning
confidence: 99%